PENYITAAN ASET PELAKU TINDAK PIDANA KORUPSISEBAGAI UPAYA PENGEMBALIAN KERUGIAN NEGARA( STUDI KASUS DI KEJAKSAAN NEGERI JAKARTASELATAN ) - Regina Rahma Utami, - (2019)
Confiscation and seizure of assets of convicted corruption is an anticipatory step that aims to save or prevent the transfer or loss of assets from convicted corruption, to be confiscated as a substitute for state losses due to criminal acts of corruption. Problems: What is the mechanism for the implementation of seizure of assets of corruption convicts by the South Jakarta District Prosecutor's Office as an effort to recover state losses and how to strengthen the state's loss of return. The method used is normative juridical approach to law and additional information and law enforcement opinions from the South Jakarta District Attorney and academics. This study resulted in findings: the mechanism for the implementation of seizure of assets of corruption convicts in the form of; asset tracking, asset freezing, asset seizure, asset seizure, and asset management.The suggestions in this study are the executive and legislative immediately ratify the draft Criminal Asset Deprivation bill into law